Semantic priming of bilingual subjects Arabic/French and monolingual French subject - Sassane, Ali (2015)
The purpose of this paper is to study the organization of the mental lexicon in semantic memory through the presentation a list of imaged and abstract words to the bilingual subjects Arabic / French and monolingual French subjects. To do this, we had used the technique of semantic priming and we asked them to write the first three words that come to mind. The technique of semantic priming has firstly revealed the existence of several types of semantic relations within the same semantic network. In addition, we noticed that there is a positive association between the words "target" and the words mentioned by our subjects because the time allotted for the experiment was observed. On the other hand, the words are organized in the memory semantic categories by inclusion of a set of equivalent words according to the taxonomic model (Collins et Loftus, 1975; Collins et Quillian, 1968, 1969). Finally, the associative strength between different items is only the reflection of the connectionist model Boutanquoi (1994), who thinks that a unit is connected to others that if a significant number of topics associated with it.